2010
DOI: 10.7881/dentalmedres.30.15
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Phenotype of Resident Macrophages in the Dental Pulp during Rat Mandibular First Molar Development

Abstract: The dental pulp is the part in the center of a tooth made up of a loose connective tissue and cells called odontoblasts. Each pulp organ is composed of a coronal pulp located centrally in the crown of teeth and the root or radicular pulp. The radicular root portion of the pulp are continuous with the periapical connective tissue through the apical foramen where blood vessels and nerve fi bers are penetrated. 1 Macrophages form heterogeneous populations with regard to their morphological, functional, phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…M2 macrophages may play a role in homeostasis maintenance of the engineered tissue, as resident macrophages do in normal dental pulp (Luke et al 2013). The localization and phenotype of the resident macrophages were reported to change during rat tooth development (Miyauchi et al 2010), which indicates a regulatory function of resident macrophages in uninflamed dental pulp. A previous study has also shown that the immunoreactivity of macrophages appeared to change during the pulpal regeneration process in injured dental pulp (Nakakura-Ohshima et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages may play a role in homeostasis maintenance of the engineered tissue, as resident macrophages do in normal dental pulp (Luke et al 2013). The localization and phenotype of the resident macrophages were reported to change during rat tooth development (Miyauchi et al 2010), which indicates a regulatory function of resident macrophages in uninflamed dental pulp. A previous study has also shown that the immunoreactivity of macrophages appeared to change during the pulpal regeneration process in injured dental pulp (Nakakura-Ohshima et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, macrophages in the rat crown dental pulp and the root pulp express nonidentical immunological profiles. Researchers have suggested that alternation from CD68 + /MHC class II − to CD68 + /MHC class II + occurs during the maturation of dental pulp macrophages (Miyauchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The dental pulp is susceptible to damage resulting from dental caries, dental trauma, and surgical procedures, amongst others. However, the dental pulp is well-equipped with several tissue-resident macrophage populations that can mount a defense response, mitigate in ammation, and accelerate the healing process [19][20][21][22] . Our previous study demonstrated the existence of a LYVE-1 + macrophage population in rat dental pulp tissue under steadystate conditions 23 .…”
Section: Introductionmentioning
confidence: 99%